Mapping gas around massive galaxies: cross-correlation of DES Y3 galaxies and Compton-y maps from SPT and Planck. Issue 2 (20th April 2023) - Sánchez, J; Omori, Y; Chang, C; Bleem, L E; Crawford, T; Drlica-Wagner, A; Raghunathan, S; Zacharegkas, G; Abbott, T M C; Aguena, M; Alarcon, A; Allam, S; et al.
ABSTRACT: We cross-correlate positions of galaxies measured in data from the first three years of the Dark Energy Survey with Compton- y maps generated using data from the South Pole Telescope (SPT) and the Planck mission. We model this cross-correlation measurement together with the galaxy autocorrelation to constrain the distribution of gas in the Universe. We measure the hydrostatic mass bias or, equivalently, the mean halo bias-weighted electron pressure 〈 bh Pe 〉, using large-scale information. We find 〈 bh Pe 〉 to be [0.16^+0.03_-0.04, 0.28^+0.04_-0.05, 0.45^+0.06_-0.10, 0.54^+0.08_-0.07, 0.61^+0.08_-0.06, 0.63^+0.07_-0.08] meV cm −3 at redshifts z ∼ [0.30, 0.46, 0.62, 0.77, 0.89, 0.97]. These values are consistent with previous work where measurements exist in the redshift range. We also constrain the mean gas profile using small-scale information, enabled by the high-resolution of the SPT data. We compare our measurements to different parametrized profiles based on the cosmo-OWLS hydrodynamical simulations. We find that our data are consistent with the simulation that assumes an AGN heating temperature of 10 8.5 K but are incompatible with the model that assumes an AGN heating temperature of 10 8.0 K. These comparisons indicate that the data prefer a higher value of electron pressure than the simulations within r 500 c of the galaxies' haloes.